ESTUDO DAS VIAS DE SINALIZAÇÃO CELULAR ENVOLVIDAS NA VASODILATAÇÃO DEPENDENTE DE ENDOTÉLIO DURANTE A PERIODONTITE EXPERIMENTAL - Olchanheski Junior, Luiz Renato (2014)
Periodontitis is defined as a disease characterized by the formation of a biofilm which promotes colonization of microorganisms responsible for the initiation of a local inflammatory process. Studies have shown that the inflammatory process is not restricted to the oral cavity, reaching the circulation and causing systemic effects, such as endothelial dysfunction. The dysfunction is mainly characterized by reduced nitric oxide production/ bioavailability which increased platelet aggregation, leukocyte adhesion and rolling, and result in a loss in the ability of vasodilation. Therefore predisposing to an increased risk of cardiovascular disease. According to research by our group, animals with experimental periodontitis showed a decrease in endothelium-dependent vasodilator response fourteen days after the induction of periodontitis, however, this reduced vasodilator response is not evident twenty one days. The purpose of this study was to evaluate a possible increase in compensatory mechanisms of vasodilation in animals with experimental periodontitis. For this, rats received ligatures for induction of periodontitis, or were sham. Twenty one days after the procedure, the animals were prepared for blood pressure recording. Two consecutive dose-response curves to acetylcholine and sodium nitroprusside were obtained before and 20 min after LNAME (NOS inhibitor) + indometacin (COX inhibitor) + TEA (selective inhibitor of potassium channels) or LNAME or indometacin, or TEA or indometacin + TEA or Apamin + TRAM-34 injection. Only the selective and simultaneous blockade of small and intermediate-conductance calcium-activated potassium channels by selective inhibitors (Apamin and TRAM-34, respectively) was able to reduce acethylcholine-induced reduction on blood pressure at periodontitis animals. The inhibition of NOS, COX and use of a non-selective inhibitor of potassium channels, did not change the endothelium-depended vasodilatation. Altogether, these results show that IKca and SKca may balance the endothelial function and therefore mask the impairment on NO production and endothelial dysfunction.